Algorithm for the treatment of external nasal valve insufficiency - Dolci,Eduardo Landini Lutaif (2020)
Abstract Introduction: Nasal obstruction is one of the most prevalent complaints in the population. The main causes of nasal obstruction are inflammatory, infectious or anatomical alterations. Anatomical alterations include nasal septum deviation, turbinate hypertrophy, and nasal valve insufficiency (external and/or internal). The diagnosis of nasal valve insufficiency remains a clinical one and is based on inspection and palpation of the nose, evaluating both its static and dynamic functions. The literature presents several options for the correction of external nasal valve insufficiency. These are chosen according to the choice and experience of each surgeon. Objective: To create a practical algorithm for the treatment of external nasal valve insufficiency that can guide nasal surgeons in their choice of treatment for the different anatomical alterations found in patients with these disorders. Methods: We used the treatment options found in the literature and correlated them with our surgical options for each type of anatomical alteration found. Therefore, we used basically three parameters related to physical examination findings (degree of insufficiency and characteristics of the lower lateral cartilage) and the patient's complaint (present or absent aesthetic complaint regarding the nasal tip). Result: A practical algorithm was developed for the treatment of external nasal valve insufficiency according to the degree of insufficiency (mild-to-moderate or severe), aesthetic complaint of the nasal tip (present or absent) and characteristics of the lower lateral cartilage (size and orientation). Conclusion: Through this simple algorithm, one can use each type of graft and/or maneuver according to the patients' complaints and the anatomical alterations found.